The Business Ethics of Kotagede’s Silver Entrepreneurs from the Kingdom to the Modern Era - Muhammad Iqbal Birsyada; Septian Aji Permana (Paramita: Historical Studies Journal)
The silver business since the reign of Sri Sultan HB VIII has gained its position in driving the economic progress of Kotagede’s people. The silver industry, besides its economic values, is also a cultural asset of the people of Yogyakarta. From 1935-1938, there were more than 78 silver entrepreneurs with a total annual production of 25 tons of silver. This study aims to determine and to analyze the history of the silver business in Kotagede and the values inherited from the kingdom period to the modern era. This research used the historical method by describing data on the development of silver business in Kotagede in a descriptive, chronological manner combined with a phenomenological approach. This research shows the success of the silver industry in Kotagede from the kingdom to the colonial era. It is supported by the collective power of the craftsmen community and silver entrepreneurs. It was also encouraged by the local government which helped to open the silver market network both at national and international levels. During the old order until the new order, the role of business actors in each founder of the silver business in building marketing networks both nationally and internationally became one of the main factors in running the silver industry in Kotagede. Third, the ethics inherited include honest, patient, simple, clean, neat, conscientious, healthy intentions, innovative, hard work.